The role and significance of curiosity in philosophy for children - Altıparmak, İrem Günhan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Philosophy for Children (P4C) is an educational movement which aims to develop children’s thinking and reasoning skills by means of engaging them in intellectual inquiry and questioning. Though P4C is predominantly based on questioning and inquiry, there is little emphasis on curiosity in the literature. Ilhan Inan’s account of curiosity could be utilized in order to demonstrate the importance of curiosity within P4C. In this thesis, the notion of inostensible conceptualization, which Inan has developed and is central to his account of curiosity, and awareness of ignorance are primarily highlighted together with bringing discussions about the value of curiosity from Virtue Epistemology as these shed light on the necessity of fostering curiosity in the sessions. In addition to this, Nermi Uygur and Luciano Floridi’s accounts of philosophical questions help for a better understanding regarding the inquiry and questions asked in the P4C discussions. Realizing the theoretical background on the concept of curiosity, I explore the roles of curiosity in P4C. In analyzing these roles, Inan and I developed two notions with an aim to enrich the literature: the first notion is curiosity-arouser, which is utilized to explain how the children as inquirers could better concentrate on and discuss the concepts philosophically. The second notion is joint-curiosity, which we have developed in analogy to the trans-disciplinary notion of joint attention. My overall aim is to address the significance of curiosity in order for this practice to reach its essential aims and emphasize the capacity of these notions by holding that they will enrich not only P4C literature but also diverse areas of studies.
Keywords: Education -- Philosophy.; Thought and thinking -- Philosophy.; Thought and thinking -- Study and teaching.